Design of precoding matrices in MIMO full duplex two-way security communication system - Weijia LEI; Yang ZHOU; Xianzhong XIE; Hongjiang LEI (Tongxin xuebao)
The design of precoding matrices was studied in the multiple input multiple output (MIMO) full-duplex two-way security communication system where legitimate nodes transmit the confidential information accompanied by the artificial noise while receiving information.For the scenario where the perfect channel state information (CSI) of legitimate channels and eavesdropping channels was available,the difference of concave/convex (DC) programming was used to optimize the precoding matrices of the information signal and the artificial noise for the maximization of the secrecy sum rate.For the scenario where the CSI was imperfect,the channels were modeled by using worst-case criterion and the weighted minimum mean square error algorithm was used to get the robust precoding matrices of the information signal and the artificial noise.The simulation results prove that the proposed algorithm can effectively promote the secrecy sum rate of the system.